Legal Certainty For Foreign Investors In Coal Mining In Indonesia - Velentina, Rouli Anita Velentina Anita (Jurnal Hukum & Pembangunan, 2019)
Since 2009, there have been significant regulatory changes in coal mining in Indonesia, beginning with the enactment of Law No.4 of 2009 concerning Mineral and Coal Mining, which replaced the prior system of contracts and mining authorizations (Kuasa Pertambangan; KP) with mining business permits (Ijin Usaha Pertambangan; IUP). There are two types of IUP: exploration and production operation. Then, the mechanism of Clean and Clear was created to reduce the large numbers of overlapping licenses. This article explores Indonesian regulatory changes and court rulings in coal mining and clarifies share divestment requirements for foreign investors in Indonesian coal-mining operations, which should not be classified as indirect expropriations.